Cardiorespiratory fitness in Chinese children and adolescents: a systematic review and meta-analysis - Yihan Meng; Yu Song; Hongjuan Li (Annals of Human Biology)
Background Cardiorespiratory fitness (CRF) has become a significant focus in the field of public health. CRF is considered a strong predictor of health outcomes. However, cardiorespiratory fitness levels of children and adolescents are declining.Aims (1) To analyse the cardiorespiratory fitness levels of children and adolescents in China, focusing on maximum oxygen uptake (VO2max), maximum heart rate (HRmax), peak oxygen uptake (Peak VO2) and 20-metre shuttle run test (20 m-SRT). (2) To provide baseline data, with the goal of supporting the development of sports programs, intervention strategies, and public health decision-making.Subjects and methods A meta-analysis was conducted using 30 studies selected from five databases.Results The average performance on 20 m-SRT for Chinese children and adolescents was 34.67 laps, with a VO2max of 46.47 ml/kg/min, HRmax of 195.02 bpm, and Peak VO2 of 48.58 ml/kg/min. Boys outperformed girls in VO2max, 20 m-SRT, and HRmax, although the differences in HRmax and Peak VO2 were not statistically significant. Tibetan children showed better performance than Han children in three indicators with no significant differences found.Conclusion Cardiorespiratory fitness in Chinese children and adolescents is within a healthy range but not optimal. Boys generally perform better than girls, and Tibetan children outperform Han children.